2014
DOI: 10.1016/j.neuron.2014.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin Signaling Regulates Neural Induction through Antagonizing the BMP Pathway

Abstract: Summary Development of the nervous system begins with neural induction, which is controlled by complex signaling networks functioning in concert with one another. Fine-tuning of the bone morphogenetic protein (BMP) pathway is essential for neural induction in the developing embryo. However, the molecular mechanisms by which cells integrate the signaling pathways that contribute to neural induction have remained unclear. We find that neural induction is dependent on the Ca2+-activated phosphatase calcineurin (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 68 publications
1
25
0
Order By: Relevance
“…It has been reported that the calcineurin regulatory subunit CnB, which binds to all CnA isoforms, is necessary for mESC differentiation to all lineages through a mechanism involving the transcription factor NFAT (Li X et al, 2011). In contrast, a recent work suggests that CnB activity may be specifically needed for ectoderm differentiation, but dispensable for mesoderm and endoderm differentiation, and that CnA controls BMP signaling by directly targeting Smad1/5 during this process (Cho et al, 2014). Knockout mice lacking the catalytic domain in CnA are born at normal mendelian ratios (Bueno et al, 2002), suggesting that the phosphatase activity of CnA is not essential for mESC differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the calcineurin regulatory subunit CnB, which binds to all CnA isoforms, is necessary for mESC differentiation to all lineages through a mechanism involving the transcription factor NFAT (Li X et al, 2011). In contrast, a recent work suggests that CnB activity may be specifically needed for ectoderm differentiation, but dispensable for mesoderm and endoderm differentiation, and that CnA controls BMP signaling by directly targeting Smad1/5 during this process (Cho et al, 2014). Knockout mice lacking the catalytic domain in CnA are born at normal mendelian ratios (Bueno et al, 2002), suggesting that the phosphatase activity of CnA is not essential for mESC differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Calcineurin also regulates neurotransmitter release and vesicle recycling through the dephosphorylation of synapsin I and dynamin I along with amphiphysin I and II (51)(52)(53). In murine and human ES cells, proper regulation of calcineurin activity is required for neural differentiation (54). In addition to its direct effects on phosphorylation, calcineurin also regulated axon terminal remodeling by regulating nuclear factor of acti-vated T cells-dependent gene transcription at the initial stage of synapse formation (55).…”
Section: Discussionmentioning
confidence: 99%
“…However, neural precursors and differentiating neurons can also be generated in the absence of RA, in serumfree medium containing insulin, transferrin and sodium selenite (referred to as serum-free ITS), and basic fibroblast growth factor (bFGF). Furthermore, neural precursors can efficiently differentiate into functional post-mitotic neurons after the withdrawal of bFGF [38] [39]. In This is the Pre-Published Version addition, it has been reported that stromal cells can promote neural differentiation; this was demonstrated when mouse ESCs were co-cultured with the bone marrow-derived stromal cell line, PA6, in serum-free conditions without the use of either RA or EB initiation [40].…”
Section: The Protocols Of Neural Differentiation Of Escsmentioning
confidence: 99%
“…TRPC1 has also been shown to contribute to the bFGF/FGFR1-induced Ca 2+ influx that regulates the proliferation of embryonic rat NSCs [88]. Most recently, a link between the FGF and BMP pathways, and Ca 2+ signaling has been identified in the form of the Ca 2+ -dependent phosphatase calcineurin (CaN) [39]. FGF can trigger TRPC3-mediated Ca 2+ entry, which results in the activation of CaN.…”
Section: Trpc Channelsmentioning
confidence: 99%
See 1 more Smart Citation